Kommunikativnye partii personažej v strukture hudožestvennoj prozy - Mečkovskaja, Nina Borisovna (Slavistična revija, 2009)
Communicative party of the literature character is created in direct speech by succession (chain) of speech acts differentiated by their illocutionary forces - such as intention to inform, to impel to do something, to express feelings and so on. Paradigmatic and syntagmatic investigation of communicative parties (relations between the direct speech and the author's speech; communicative completeness or incompleteness of dialogs and polylogs; the variety of speech acts, their quantitative hierarchy in communicative parties of different literature characters and so on) gives good opportunities to understand as well literature characters as well the reflection speech communication in fiction communication (that is also impotent for the general ontology of speech act in reality).
Keywords: German-language literature; literarne osebe; nemška književnost; pomenoslovje; ruska književnost; Russian literature